Fear: Introduction to special issue. (August 2021) - Hill, Annette; Mortensen, Mette; Hermes, Joke
Fear needs dealing with. Fear demands to be abated, countered or turned into something else, contributing and curtailing how we 'do' being human beings. This special issue of the European Journal of Cultural Studies addresses fear within media and popular culture, adopting a cultural studies approach to fear in a variety of socio-cultural and political contexts. A cultural studies approach allows us to enhance the horizon of understanding cultural practices, mediation and the subjective experience of fear as something we need to work through, in a process of recognition and shock, action and reaction, understanding and reflection. This focus on 'working through fear' offers new insights into the intensely subjective aspects of fear as it is creatively explored in representations within drama and documentary, photography and art, and in user-generated content, memes and political satire, and as it is embodied and experienced by people in the context of their realities. In addition, it shows how fear generates energy, anxiety and even desire. Rather than offering a generalizing account, this issue seeks to address fear in specific contexts, localities and from specific roles and perspectives.